2013
DOI: 10.1017/s1041610212002293
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life instruments for Alzheimer's disease and mixed dementia

Abstract: Background: Over the last 20 years, a number of instruments developed for the assessment of health-related quality of life (HRQL) in dementia have been introduced. The aim of this review is to synthesize evidence from published reviews on HRQL measures in dementia and any new literature in order to identify dementia specific HRQL instruments, the domains they measure, and their operationalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 81 publications
3
66
0
Order By: Relevance
“…The present study confirms that QOL should be approached and measured as a multidimensional construct and not as a single construct [8]. The study also shows that it is possible to detect which people are at risk for a lower QOL across different QOL domains.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The present study confirms that QOL should be approached and measured as a multidimensional construct and not as a single construct [8]. The study also shows that it is possible to detect which people are at risk for a lower QOL across different QOL domains.…”
Section: Discussionsupporting
confidence: 82%
“…Different observational methods are available and validated to measure QOL in persons with moderate to severe dementia in LTCFs [7,50,51,52,53], and some have good psychometric properties [8,9]. These observational instruments employ different domains of QOL that are important for persons with dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that subscale scores should be calculated because HRQL by definition is a multidimensional concept and respective domain scores might help clarify treatment impact [5, 83]. However, the current study suggests that after controlling for general HRQL, subscales in DEMQOL and DEMQOL-Proxy explain little more and have poor score reliability, and therefore should not be used.…”
Section: Discussionmentioning
confidence: 71%
“…In a recent systematic review that compared psychometric properties of HRQL measures for Alzheimer’s disease and mixed dementia, the authors found 15 dementia-specific HRQL measures developed over the last 20 years [5]. The basis for measuring HRQL varies between instruments with different representations of what might be considered ‘good’ or ‘bad’ quality-of-life.…”
Section: Introductionmentioning
confidence: 99%